Feeding habits of juvenile Chacophrys pierottii (Ceratophryidae-Ceratophryinae) From northwestern Córdoba province, Argentina - Pueta, Mariana (2013)
the Chacoan burrowing Frog Chacophrys pierottii (Ceratophryidae-Ceratophryinae) is an endemic species of the Chaco region in south america. there is scarce information about the biology of the species and limited information about its post-metamorphic stages. in this work we determined the diet of juvenile C. pierottii and estimated the relative importance of the different prey items. we also evaluated relationships between the volume of consumed prey and three morphological features of the frogs: snout-vent length, jaw length, and jaw width. analysis of 20 stomachs with identifiable prey from a set of 75 frogs collected showed that coleopterans and hymenopterans were the dominant prey items, although the diet also included frogs, insect larvae, dipterans, hemipterans, spiders, and scorpions. we also report cannibalism in C. pierottii. this species is a generalist predator similar to some other members of the subfamily. we found no associations between prey volume and the three morphological feature of predator size.